Closure of Perimembranous Ventricular Septal Defects with Intraoperative Device Technique: Another Safe Alternative to Surgical Repair - Chen, Qiang; Cao, Hua; Zhang, Gui-Can; Chen, Liang-Wan; Li, Qian-Zhen; Qiu, Zhi-Huang (The Thoracic and Cardiovascular Surgeon, 2013)
Objectives This study aims at assessing the safety and feasibility of intraoperative device closure of the perimembranous ventricular septal defect (VSD).Methods Total 89 patients in group I with intraoperative device closure and 58 in group II with surgical repair were enrolled in our hospital to participate in the study from January 2009 to December 2010. In group I, the approach involved a minimal inferior median incision that was performed after full evaluation of the perimembranous VSD by real-time transesophageal echocardiographic guidance, and the insertion of an asymmetric or a symmetric domestically made device was used to occlude the perimembranous VSD.Results In group I, 83 patients were occluded successfully under this approach. The size of the occluder implanted ranged from 6 to 14 mm. Complete atrioventricular block occurred in one case and Mobitz type II atrioventricular block occurred in one case during the procedure. One patient presented complete atrioventricular block one week after the operation. Two patients converted to surgical repair because of severe intraoperative aortic valve regurgitation. One patient with significant residual shunt transformed to surgical treatment. In our comparative studies, patients in group II experienced significantly longer operative time, ICU stay, and hospital stay (p < 0.001). The cost of group I was less than that of group II (p < 0.001).Conclusions Minimally invasive transthoracic device closure of the perimembranous VSD with an asymmetric or a symmetric domestically made device without cardiopulmonary bypass is safe and feasible. It should be considered an acceptable alternative to surgery in selected subgroups. However, it is necessary to evaluate the long-term results.
Keywords: CHD; septal defects; cardiac intervention; surgery